Chapter Economic Instruments to Combat Eutrophication: A Survey - Terreaux, Jean-Philippe (InTechOpen, 2019)
Eutrophication of aquatic ecosystems is a functional process triggered by excessive nutrient inputs into water courses. It causes disruption to ecosystems, with impacts on associated goods and services, which consequently might not be provided in a sustainable way. These impacts have served to politicize the issue in recent years. In this chapter, we present the main lessons learned from an international literature review on the economic aspects of eutrophication, first with the purpose of managing the problem in France and second in the context of a European research project. This study aims to help public decision-making in the reduction of this water pollution. By analyzing past experiences and the results of recent modeling work, it allows to avoid a number of pitfalls and focus on efficient solutions.